The Choice between Buying Offices and Buying Agents: How to maximize the value added in the global sourcing activities in the clothing industry - Tong, Wing-Si-Cecilia (2016)
The purpose of this dissertation is to investigate the trend in adoption of two types of external intermediaries in clothing industry: buying office and buying agent. Limited research has been conducted on the classification of different types of clothing supply network, but this dissertation seeks to differentiate the value added in global sourcing activities of buying office and buying agent. A comprehensive case study is conducted to investigate one buying office and one buying agent that based in Hong Kong, using a new nine-factors global sourcing framework to compare extensively the performance and specialties of each type of intermediary. This dissertation successfully differentiates the functions and characteristics of buying office and buying agent, recognising a trend of adopting intermediaries based on a brand’s development, service expectation from intermediaries and external influences. This observed trend is applicable for all clothing retailers, intermediaries and prime manufacturers.